Out of Nowhere Into Nothing - Pagel, Caryl (Book collections on Project MUSE., 2020)
"Out of Nothing into Nowhere by Caryl Pagel is a collection of essays that blends memoir, research, and lyrical reflection, driven by a desire to observe and see connections, though always anchored in real places, people, and conflicts"--